Randomized, parallel placebo-controlled trial of primaquine for malaria prophylaxis in Papua, Indonesia. - Baird, J; Lacy, MD; Basri, H; Barcus, M; Maguire, J; Bangs, M; Gramzinski, R; Sismadi, P; Krisin; Ling, J; Wiady, I; Kusumaningsih, M; et al. (2001)
Malaria causes illness or death in unprotected travelers. Primaquine prevents malaria by attacking liver-stage parasites, a property distinguishing it from most chemoprophylactics and obviating 4-week postexposure dosing. A daily adult regimen of 30 mg primaquine prevented malaria caused by Plasmodium falciparum and P. vivax for 20 weeks in 95 of 97 glucose-6-phosphate dehydrogenase (G6PD)-normal Javanese transmigrants in Papua, Indonesia. In comparison, 37 of 149 subjects taking placebo in a parallel trial became parasitemic. The protective efficacy of primaquine against malaria was 93% (95% confidence interval [CI] 71%-98%); against P. falciparum it was 88% (95% CI 48%-97%), and >92% for P. vivax (95% CI >37%-99%). Primaquine was as well tolerated as placebo. Mild methemoglobinemia (mean of 3.4%) returned to normal within 2 weeks. Blood chemistry and hematological parameters revealed no evidence of toxicity. Good safety, tolerance, and efficacy, along with key advantages in dosing requirements, make primaquine an excellent drug for preventing malaria in nonpregnant, G6PD-normal travelers.